Standing tall : leadership lessons in the life of a soldier - Foley, Robert F., 1941- (Tantor Media, Inc., 2022)
Robert Foley had only been in Vietnam for six months when he was promoted to captain and given command of a rifle company. In November 1966, Foley led his men on a mission to rescue another company that had been pinned down by Viet Cong forces. His leadership that day inspired his men and led to a successful operation-and the Medal of Honor. His actions in Vietnam were only a small portion of a long and varied career of service in the US Army, but Foley did not always seem marked for success. Coming from a blue-collar suburb of Boston, his years in West Point were marked by poor grades, injuries, and sickness. With a determination to lead by example and inspire trust among others, Foley served across the globe and rose through the ranks. He even returned to West Point as Commandant of Cadets, later retiring as a 3-star general and commander of Fifth Army.